(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Nanofluid is crucial for improving heat conduction in nuclear power plants. It opens up new opportunities for improving heat transfer and reducing thermal hydraulics problems in nuclear reactors. The purpose of this research is to quantitatively illustrate the heat transfer performance of a CuO/Water-based nanofluid in a light water nuclear reactor. The hexagonal form of the nuclear fuel rod assembly’s 1/6th was used in this study’s modelling. The thermal properties of conventional fluid are improved using CuO/water nanofluid. A constant heat flux is applied to the inner wall. The link between nanofluid flow rate and nanoparticle concentration is shown by profiles of the temperature near to the wall and the heat transfer coefficient. The amount of heat that a nanofluid can transport may depend on its volume concentration, physical properties, and nanoparticle size. Density, thermal conductivity, specific heat, and viscosity were investigated and utilised as the fundamental data for ANSYS 19. In order to increase the precision of the findings, the k-SST turbulence model is investigated. Two volumes of concentration—1% and 2%—are used in this numerical study. Results are compared to mathematical formulae for heat transmission. The results show that a single phase model significantly improves predictions of heat transport in nanofluids. The Reynold Number enhances the heat transfer coefficient, according to the results. It also demonstrates that the temperature near the wall is dropping as a result of the nanoparticle addition